Gas‐emission craters of the Yamal and Gydan peninsulas: A proposed mechanism for lake genesis and development of permafrost landscapes. (15th July 2019) - Dvornikov, Yury A.; Leibman, Marina O.; Khomutov, Artem V.; Kizyakov, Alexander I.; Semenov, Petr; Bussmann, Ingeborg; Babkin, Evgeny M.; Heim, Birgit; Portnov, Alexey; Babkina, Elena A.; Streletskaya, Irina D.; Chetverova, Antonina A.; et al.
Abstract: This paper describes two gas‐emission craters (GECs) in permafrost regions of the Yamal and Gydan peninsulas. We show that in three consecutive years after GEC formation (2014–2017), both morphometry and hydrochemistry of the inner crater lakes can become indistinguishable from other lakes. Craters GEC‐1 and AntGEC, with initial depths of 50–70 and 15–19 m respectively, have transformed into lakes 3–5 m deep. Crater‐like depressions were mapped in the bottom of 13 out of 22 Yamal lakes. However, we found no evidence that these depressions could have been formed as a result of gas emission. Dissolved methane (dCH4 ) concentration measured in the water collected from these depressions was at a background level (45 ppm on average). Yet, the concentration of dCH4 from the near‐bottom layer of lake GEC‐1 was significantly higher (824–968 ppm) during initial stages. We established that hydrochemical parameters (dissolved organic carbon, major ions, isotopes) measured in GEC lakes approached values measured in other lakes over time. Therefore, these parameters could not be used to search for Western Siberian lakes that potentially resulted from gas emission. Temperature profiles measured in GEC lakes show that the water column temperatures in GEC‐1 are lower than in Yamal lakes and in AntGEC – close to values of Gydan lakes. Given the initial GEC depth > 50 m, we suggest that at least in GEC‐1 possible re‐freezing of sediments from below might take place. However, with the present data we cannot establish the modern thickness of the closed talik under newly formed GEC lakes.